2016
DOI: 10.1021/acs.analchem.6b00513
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Diffusion within Nanoarrays

Abstract: The direct experimental characterization of diffusion processes at nanoscale remains a challenge that could help elucidate processes in biology, medicine and technology. In this report, two experimental approaches were employed to visualize ion diffusion profiles at the orifices of nanopores (radius (ra) of 86 ± 6 nm) in array format: (1) electrochemically assisted formation of silica deposits based on surfactant ion transfer across nanointerfaces between two immiscible electrolyte solutions (nanoITIES); (2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
(97 reference statements)
2
16
0
Order By: Relevance
“…The growing interest for the use of silica-based materials at the liquid-liquid interface is also due to their favourable adsorption kinetics and selectivity [28], which could be harnessed to the development of new sensing methods [29,30]. ITIES was modified by the electrogeneration of mesoporous silica deposits [31][32][33][34][35], which were the result of an electrochemically driven ion transfer followed by interfacial precipitation. Mesoporous silica was generated at the ITIES by the transfer of a cationic surfactant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest for the use of silica-based materials at the liquid-liquid interface is also due to their favourable adsorption kinetics and selectivity [28], which could be harnessed to the development of new sensing methods [29,30]. ITIES was modified by the electrogeneration of mesoporous silica deposits [31][32][33][34][35], which were the result of an electrochemically driven ion transfer followed by interfacial precipitation. Mesoporous silica was generated at the ITIES by the transfer of a cationic surfactant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this improvement, the signal measured at such nanoarrays was only half of the value expected for such devices [186,187]. This discrepancy between experimental observations and theoretical calculations were due to the overlap of the diffusion zones for densely packed nano-interfaces (see Figure 9A), while widely spread interfaces showed independent diffusion profiles (see Figure 9B) [115]. By increasing the ratio pore-topore separation (S) / pore radius (r), the sensitivity increased and limits of detection improved until they reach a plateau for ratio values greater than 56 [188]; leading to the detection of 0.8 µM of propranolol using a moderately sensitive technique such as linear sweep voltammetry [189].…”
Section: Nano-itiesmentioning
confidence: 84%
“…It was also found that silica deposits can be stabilized and reused once proper support was employed. Silicon wafers patterned with an array of micro or nano pores each supporting the ITIES were modified as shown on Figure 5B and Figure 6B,D respectively [113,115]. Interestingly, the shape of resulting silica deposits was found to be a print out of the diffusion zones of CTA + on the aqueous site of the liquidliquid interface.…”
Section: Silica Materialsmentioning
confidence: 99%
“…SECM-AFM uses a probe that has topographical resolution based on the size and shape of the sharp AFM tip and electrochemical imaging resolution based on the geometry of the surrounding electrode (Figure 1f). This technique has been used to study ionic diffusion at nanopores, simultaneously with electrochemical currents associated with flux of species through the pores (SECM) and the pore topography/spacing (AFM) [41].…”
Section: Constant-distance Imaging Modesmentioning
confidence: 99%